Material Characteristics and Electrochemical Performance of YxBa2-XCo2O5+δ Cathode for Solid Oxide Fuel Cell. (2nd June 2015) - Hung, I-Ming; Wang, Jeng-An; Kuo, Jen-Yuan; Lin, Tai-Nan
Abstract : A new Y0.8 Ba1.2 Co2 O5+δ cathode was successfully prepared by solid-state reaction method. The structure, microstructure, conductivity, coefficient of thermal expansion and electrochemical properties of the Y0.8 Ba1.2 Co2 O5+δ cathode was conducted by XRD, SEM, 4 DC four-terminal method, thermal gravity analysis and thermomechanical analysis, respectively. The double perovskite structure Y0.8 Ba1.2 Co2 O5+δ with YBa2 Co3 O9-δ second phase was observed in XRD pattern. The conductivity of Y0.8 Ba1.2 Co2 O5+δ sample increased as temperature increased with a p-type conductor characterization. The Y0.8 Ba1.2 Co2 O5+δ had a maximum conductivity of 240 S/cm at 350 o C. The coefficient of thermal expansion is 19.1 x 10 -6, which is close to that of Samaria-doped Ceria (SDC) electrolyte. The Y0.8 Ba1.2 Co2 O5+δ did not react with SDC electrolyte below 950 o C. The Y0.8 Ba1.2 Co2 O5+δ is a potential cathode material for intermediate temperature solid oxide fuel cell.